A objetivação da mulher surda na ordem do digital: discursos e sentidos sobre o sujeito-corpo (de) Natália - ANA PAULA SAFFE MENDES (2021)
Under the light of the Foucault's Discursive Studies, in a dialogue between the French philosopher's concepts and the Deaf Studies (SKLIAR, 2015), I analyzed how the characterization of the deaf woman happened by the objectivization and objectification of the body in comments made in two articles published by news portal Portal G1, one from 2014, the other from 2017. For that I considered, by the archeogenealogical method's perspective, how and why did determined discursivities about Natália's life, a deaf woman, emerged. Observing the circulation of the ordinary speeches (SILVEIRA, 2016), my focus was the relation between the set knowledge about the deaf woman and the objectivization of the subject Natália in the selected comments for analysis. The construction of the archive and the corpus cut, guided by serial regularity of enunciabilities about Natália's corporeity (SANTOS, 2014) counted on the heterogeneity of discursive spaces that belong to what Guilhaumou & Maldidier (2014) call thematic trajectory. The methodology was fundamental to reading different instances of legitimacy from where rise the constitutive speeches of the collected enunciates. The possibility conditions (FOUCAULT, 2020a) of the selected object are set from 2014, with the beginning of the intensification of the debate about accessibility in the Exame Nacional do Ensino Médio, as of Natália's complaint, mediatized by Portal G1, and continue until 2017 - the year when the composition's subject focused on the difficulties of deaf people education in the Brazilian educational system and Natália starred other article of the same vehicle. From the analysis, the presence of qualitative characteristics of a deaf woman's body are highlighted, taken as, in the echo of foucaultian speeches, effects that formulate the subject Natália as disabled, problematic and sexual object. Having body and behavior regulated by normative descriptions, institutionalized by clinical, juridical, media and ordinary speeches, erasing the difference in deafness strips Natália of her heterogenic existence, overestimating the homogeneity of the naturalization of what it is being deaf by these speeches' perspective. Finally, from the analysis, this work presents itself with a contribution for scientific research expansion referring to the deaf woman. Keywords: Deaf woman. Enunciate. Objectivization. Objectification.